(untitled) (Research, Society and Development, 2021)
The study aims to map the psychosocial risks to which federal civil servants in an educational institution are exposed and to build, together with workers, strategies for coping with psychosocial risks related to work. This is a quantitative-qualitative, evaluative study, in a sample of 97 civil servants from an educational institution. There was a moderate risk for prescribed work organization, with physical space being the agent with the highest psychosocial risk; the predominance of the managerial style becomes a risk factor, while disorganization of the environment with changes, unequal opportunities for growth and tolerance to individualism were agents of high psychosocial risk. As for the suffering and illness of the employees, there was a moderate risk for mental exhaustion and the development of work-related physical damage. Defensive strategies were identified, and those that help solve the cause of suffering and indirect strategies that help eliminate drive energy should be encouraged. Investment suggestions emerged from the employees’ speech, such as training, change in organizational culture, mapping of processes and competencies, investments in infrastructure and communication. It is essential to extend this analysis to the other units of the institution, carrying out a global analysis of psychosocial risks, contributing to the promotion of workers’ mental health.